Detachable Tactile Sensor Skin Module for Robotic Applications - Lee, An Yong; Kim, Doik (2013 10TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS AND AMBIENT INTELLIGENCE (URAI), 2013)
The paper has suggested a detachable and attachable tactile sensor skin as a form of module for robotic applications. The proposed sensor skin is able to find out both the contact location and the contact force at the same time. Also the experimental result shows the effectiveness of the proposed 8x8 tactile sensor skin.